PENERAPAN STRATEGI BELAJAR AKTIF TIPE GIVING QUESTION AND GETTING ANSWER (GQGA) DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI PARIWISATA SMKN 6 PADANG TAHUN PELAJARAN 2013/2014 - Yani, Amelia Lesvivi; Rahmi, Rahmi; Suryani, Mulia (STKIP PGRI Sumbar, 2013)
The research is motivated by the fear of asking students and issue an opinion on the matter is not yet understood and a low student comprehension of mathematical concepts. This study aims to assess the development of the math concept comprehension and determine whether the student math concept comprehension by applying strategies active learning type Giving Question and Answer Getting accompanied quiz better math concept comprehension that students using conventional teaching class XI Tourism student of SMKN 6 Padang. This type of research is experimental research. The population in this study were students of class XI BU1, XI TKK, BO2 XI, XI PH2 listed in the Academic Year 2013/2014. Technique of random sampling, which was chosen as the experimental class XI BU as a control class XI TKK. The instrument used is the final test learning in the form of essays. The data analysis technique used is the t-test of the parties with MINITAB software. Based on the analysis of data obtained with P-value less than 0.015, the research hypothesis is accepted so that we can conclude the development of students math concept comprehension better by applying strategy active learning type Giving and Getting Answers Question with quiz and students math concept comprehension by implementing strategies active learning type Giving Question and Answer Getting a better math concept comprehension students with conventional learning at the level of 95%.